Otimização de parâmetros via metaheuristicas populacionais e validação de um controlador de estrutura variável - Bertachi, Arthur Hirata (2014)
This work presents the application of particle swarm optimization and ant colony optimization in the parameters optimization of a non-linear controller with variable structure based on generalized minimum variance control. This controller is composed of two parts: linear and non-linear. The non-linear term of the controller consists of two parameters that directly affects the control action, and are obtained by trial and error. Metaheuristic methods were applied to find out the optimized values of these parameters. The cost function used in metaheuristic methods takes account the error and the control signal. A numerical example of the design of this controller is also presented. Three practical experiments were considered: a servomechanism velocity control and two control loops in a didactic industrial plant, level and flow control. Experimental results emphasize the improvement of the system performance when the optimization methods are applied. A comparision with PI controller is shown.